Evidence for halogen bond covalency in acyclic and interlocked halogen-bonding receptor anion recognition. - Robinson, S; Mustoe, C; White, N; Brown, A; Thompson, A; Kennepohl, P; Beer, P (American Chemical Society, 2015)
The synthesis and anion binding properties of novel halogen-bonding (XB) bis-iodotriazole-pyridinium-containing acyclic and [2]catenane anion host systems are described. The XB acyclic receptor displays selectivity for acetate over halides with enhanced anion recognition properties compared to the analogous hydrogen-bonding (HB) acyclic receptor. A reversal in halide selectivity is observed in the XB [2]catenane, in comparison to the acyclic XB receptor, due to the interlocked host's unique three-dimensional binding cavity, and no binding is observed for oxoanions. Notable halide anion association constant values determined for the [2]catenane in competitive organic-aqueous solvent mixtures demonstrate considerable enhancement of anion recognition as compared to the HB catenane analogue. X-ray crystallographic analysis of a series of halide catenane complexes reveal strong XB interactions in the solid state. These interactions were studied using Cl and Br K-edge X-ray Absorption Spectroscopy (XAS) indicating intense pre-edge features characteristic of charge transfer from the halide to its bonding partner (σ(AX←X(-))(*) ← X1s), and providing a direct measure of the degree of covalency in the halogen bond(s). The data reveal that the degree of covalency is similar to that which is observed in transition metal coordinate covalent bonds. These results are supported by DFT results, which correlate well with the experimental data.